Changes in Hypothalamus–Pituitary–Adrenal Axis Following Transient Ischemic Attack. (September 2014) - Radak, Djordje; Resanovic, Ivana; Isenovic, Esma R.
Acute brain ischemia caused by transient ischemic attack initiates a complex sequence of events in the central nervous system and hypothalamic–pituitary–adrenal (HPA) axis which may ultimately culminate in neuronal and cell damage. The brain is highly susceptible to ischemia and in response to stress shows changes in morphology and chemistry that are largely reversible. These responses are known to modify the function of the HPA axis, but their mechanisms are not yet clear. Duration and size of the HPA axis activation are regulated by corticotropin-releasing hormone, vasopressin (AVP), and glucocorticoids, including cortisol. Numerous studies suggest that activation of these hormones following brain ischemia can result in neurohormonal dysfunction that can exacerbate long-term prognosis following stroke. These studies represent evidence that changes in the HPA axis play an important role in brain ischemia.